Gene Banks as Reservoirs to Detect Recent Selection: The Example of the Asturiana de los Valles Bovine Breed - Boitard, Simon; Paris, Cyriel; Sevane, Natalia; Servin, Bertrand; Bazi-Kabbaj, Kenza; Dunner, Susana (Frontiers in Genetics, 2021)
Gene banks, framed within the efforts for conserving animal genetic resources to ensure the adaptability of livestock production systems to population growth, income and climate change challenges, have emerged as invaluable resources for biodiversity and scientific research. Allele frequency trajectories over the few last generations contain rich information about the selection history of populations, which cannot be obtained from classical selection scan approaches based on present time data only. Here we apply a new statistical approach taking advantage of genomic time series (Paris et al. 2019) and a state of the art statistic (nSL) based on a present time data, to disentangle both old and recent signatures of selection in the Asturiana de los Valles cattle breed. This local Spanish breed native to Asturias and originally multipurpose, has been selected towards beef production over the last generations. With the use of SNP chip and whole-genome sequencing (WGS) data, we detect candidate regions under selection reflecting the effort of breeders to produce economically valuable beef individuals, e.g. by improving carcass and meat traits with genes such as MSTN, FLRT2, CRABP2, ZNF215, RBPMS2, OAZ2 or ZNF609, while maintaining the ability of thriving under a semi-intensive production system, with selection at immune (GIMAP7, GIMAP4, GIMAP8, TICAM1) or olfactory receptor (OR2D2, OR2D3, OR10A4, 0R6A2) genes. This kind of information will allow to take advantage of the invaluable resources provided by gene bank collections from local, less competitive breeds, enabling the livestock industry to exploit the different mechanisms fine-tuned by natural and human-driven selection on different populations to improve productivity.